Presentation and management of postcircumcision meatal stenosis at Hawari Center, Benghazi, Libya: A clinical review of 86 cases - Elkhafifi, Muftah (Libyan International Medical University Journal, 2019)
Background: Circumcision is a commonly practiced surgical procedure particularly in Islamic countries. As any other surgical procedure, it is attended by some complications of either early (e.g., bleeding) or late (e.g., meatal stenosis [MS]). Objectives: This study was designed to study the different clinical pictures, age at presentation, and management and outcome of postcircumcision MS. Patients and Methods: This is a retrospective study involving 86 children diagnosed with symptomatic MS and underwent meatotomy during the period from January 2010 to December 2018 at Hawari Center for Urology and Otolaryngology, Benghazi. The medical records of the patients reviewed included age at presentation, different clinical pictures, management, and outcomes. All patients were circumcised during the neonatal or infancy period. Results: Patients' age ranged between 3 and 13 years with a mean age of 5.14 years. More than three-quarters of the patients (84.8%) were between 3 and 8 years of age. Forty-six patients (53.4%) presented with pain (burning) during micturition; 17 patients (19.7%) with thin casting stream; 13 patients (15.11%) with thin dorsally deviated stream; five patients (5.8%) with sudden urge to micturiate; 3 (3.40%) patients with frequency of micturition; and only two patients (2.3%) with prolonged voiding time. All our patients operated by meatotomy as a day case procedure under general anesthesia, and there were no recurrences of MS symptoms in any case during the follow-up period. Conclusion: MS is a frequent late complication of neonatal circumcision; it should be excluded by careful meatal examination in any child who is circumcised particularly at the neonatal or nappy period and presented with abnormal micturition or even lower abdominal pain.
Keywords: Circumcision; complications; meatal stenosis; neonatal